A Ubiquitous Illusion of Volume: Are Impressions of 3D Volume Captured by an "Additive Heuristic"?. (May 2021) - Bennette, Elizabeth; Keil, Frank C.; Yousif, Sami R.
Several empirical approaches have attempted to explain perception of 2D and 3D size. While these approaches have documented interesting perceptual effects, they fail to offer a compelling, general explanation of everyday size perception. Here, we offer one. Building on prior work documenting an "Additive Area Heuristic" by which observers estimate perceived area by summing objects' dimensions, we show that this same principle—an "additive heuristic"—explains impressions of 3D volume. Observers consistently discriminate sets that vary in "additive volume, " even when there is no true difference; they also fail to discriminate sets that truly differ (even by amounts as much as 30%) when they are equated in "additive volume." These results suggest a failure to properly integrate multiple spatial dimensions, and frequent reliance on a perceptual heuristic instead.